Semiconductor double quantum dot micromaser - Liu, Y. -Y.; Stehlik, J.; Gullans, M. J.; Taylor, J. M.; Petta, J. R.; Eichler, Christopher (Science, 2015)
The coherent generation of light, from masers to lasers, relies upon the specific structure of the individual emitters that lead to gain. Devices operating as lasers in the few-emitter limit provide opportunities for understanding quantum coherent phenomena, from terahertz sources to quantum communication. Here we demonstrate a maser that is driven by single-electron tunneling events. Semiconductor double quantumdots (DQDs) serve as a gain medium and are placed inside a high-quality factor microwave cavity. We verify maser action by comparing the statistics of the emitted microwave field above and below the maser threshold.
CRIS-Team Scopus Importer:2022-06-27